Neurorights in History: A Contemporary Review of José M. R. Delgado’s “Physical Control of the Mind” (1969) and Elliot S. Valenstein’s “Brain Control” (1973) - Schleim, Stephan (Frontiers in Human Neuroscience, 2021)
Scholars from various disciplines discuss the ethical, legal, and social implications of neurotechnology. Some have proposed four concrete “neurorights”. This review presents the research of two leaders in brain stimulation in the 1950s to 1970s, José M. R. Delgado and Elliot S. Valenstein, who also reflected upon the ethical, legal, and social aspects of their and other scientists’ related research. Delgado even formulated the vision “toward a psychocivilized society” where brain stimulation is used to control, in particular, citizens’ aggressive and violent behavior. Valenstein, by contrast, believed that the brain is not organized in such a way to allow the control or even removal of only negative processes without at the same time diminishing desirable ones. The paper also describes how animal and human experimentation on brain stimulation was carried out in that time period. It concludes with a contemporary perspective on the relevance of neurotechnology for neuroethics, neurolaw, and neurorights, including two contemporary examples for brain-computer interfaces.